Diskresi Hakim Pengadilan Agama Kotobaru Solok Terhadap Nafkah Isteri dan Hak Asuh Anak Dalam Hukum Keluarga Islam - Yesi Marlina; Sri Yunarti; Farida Arianti; Zulkifli Zulkifli; Nofialdi Nofialdi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
This study aims to conduct an in-depth analysis of the discretion of judges at the Kotobaru Solok Religious Court in determining the amount of alimony for wives and child custody in divorce cases. This study also evaluates the driving and inhibiting factors faced by judges in exercising this discretion, by examining the alignment of their decisions with the principles of Islamic family law. The research method employed was qualitative field research. Primary data sources were obtained through direct interviews with the Panel of Judges, while secondary data were sourced from official divorce case documents at the Kotobaru Solok Religious Court. Data collection techniques included observation, interviews, and documentation, which were then analyzed using domain, taxonomic, and conventional analysis methods, and strengthened by source and time triangulation techniques to ensure data validity. The results indicate that the application of judges' discretion in determining alimony for wives after a divorce is significantly influenced by the dynamics of the parties' social and economic conditions. Judges strive to strike a balance between the husband's financial capabilities and the wife's basic needs, based on the principles of maqasid sharia, particularly in maintaining the safety of life (hifz an-nafs) and protecting property (hifz al-mal). Regarding child custody, judicial discretion is fully oriented toward the best interests of the child to ensure a healthy physical and emotional growth and development environment, in accordance with the principle of hifz an-nasl. Decisions made through this discretion aim to achieve balanced, substantial justice for all parties without disregarding Quranic principles, such as Surah At-Talaq verse 7, which emphasizes providing maintenance according to one's ability. Integrally, the practice of discretion at the Kotobaru Solok Religious Court has proven consistent in protecting the rights of vulnerable wives and children within the framework of Islamic law.